Transverse Momentum Spectra of Inclusive B Jets in Ppb Collisions at √snn=5.02 Tev - Khachatryan, V.; Karapınar, Güler; Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; de Trocóniz, J.F. (Elsevier B.V., 2016)
We present a measurement of b jet transverse momentum (pT) spectra in proton-lead (pPb) collisions using a dataset corresponding to about 35 nb−1 collected with the CMS detector at the LHC. Jets from b quark fragmentation are found by exploiting the long lifetime of hadrons containing a b quark through tagging methods using distributions of the secondary vertex mass and displacement. Extracted cross sections for b jets are scaled by the effective number of nucleon–nucleon collisions and are compared to a reference obtained from PYTHIA simulations of pp collisions. The PYTHIA-based estimate of the nuclear modification factor is found to be 1.22±0.15(stat+syst pPb)±0.27(syst PYTHIA) averaged over all jets with pT between 55 and 400 GeV/c and with |ηlab|<2. We also compare this result to predictions from models using perturbative calculations in quantum chromodynamics. © 2016 CERN for the benefit of the CMS Collaboration
Keywords: B-Tagging; Cms; Heavy Ions; Physics